An Unusual Case of Ameloblastoma arising from Dentigerous Cyst - Nagarajappa, Anil K; Pandya, Divya; Jain, Nidhi (Journal of Orofacial Research, 2015)
Ameloblastoma is a benign odontogenic neoplasm that frequently affects the mandible. The term “ameloblastoma” includes several clinicoradiological and histological types. Apart from the most commonly encountered clinicopathologic models, there are few variants, whose biological profile is unknown or not elicited. Among these types, unicystic ameloblastoma is the least encountered variant of ameloblastoma. Unicystic ameloblastoma refers to those cystic lesions that show clinical, radiographic, or gross features of a jaw cyst, but on histologic examination show a typical ameloblastomatous epithelium lining the cyst cavity with or without luminal and/or mural tumor proliferation. Ameloblastoma has been reported to arise from a dentigerous cyst on rare occasions. In this paper, a case of ameloblastoma arising from epithelium of a dentigerous cyst is presented in light of the histopathologic findings, providing evidence for  ameloblastomatous change in the preexisting cyst in a 40-year-old female.